Accuracy experiment of ISO DIS 23351-1 – speech level reduction of furniture ensembles and enclosures. (July 2020) - Hongisto, Valtteri; Keränen, Jukka; Hakala, Jarkko
Abstract: An international draft standard ISO DIS 23351-1 (2019) describes a laboratory method for declaring the speech level reduction D S, A of furniture ensembles (such as partially enclosed pods or workstations) and enclosures (such as phone booths). Such products are increasingly used in e.g. open-plan offices to provide local places of improved speech privacy or concentration. D S, A describes how much the product reduces the A-weighted sound power level of standard speech to the exterior space. The method is based on repeated application of ISO 3741 standard. The purpose of our study was to determine the precision of the ISO DIS 23351-1 method for two extreme kinds of products that the method covers: a workstation and a phone booth. Eight independent laboratories from six countries participated in the accuracy experiment. Two specimens were circulated in these laboratories and tested according to ISO DIS 23351-1. The values of D S, A varied from 3.7 to 5.5 for the workstation and from 27.2 to 30.3 dB for the booth. The corresponding reproducibility standard deviations were 0.6 and 1.1 dB, respectively. The repeatability standard deviation was under 0.2 dB based on five repeated tests in a single laboratory. The results can be exploited in the development of ISO 23351-1 standard and in related test reports.